E- Government Trust Model To Enhance The Usage Of E-Government Among End-Users In Iraq - Al Nidawi, Ban Qasim Jawad (2020)
Consistent with the development and widespread usage of Information and Communication Technologies, countries around the world, including Iraq has adopted e-government to facilitate government services to its citizens. Consequently, they have been continuously seeking ways to ensure the widespread and sustainable usage of the e-government services among the citizens. However, several challenges have been identified that limit the usage of e-government among its users. Considering trust is one of the most important determiners of the usage of e-government among users, this study aims to develop an e-government trust model (EGOV-TRUST) that enhances the usage of e-government among users. Adopting the integration of UTAUT2 and TOE, specifically the individual, technological, organizational and environmental factors (I-TOE) as the lens for developing this trust model, this study focuses on three objectives, which are firstly, to analyse the constituents of trust that influence the usage of e-government; secondly, to propose the e-government trust model; and thirdly, to validate the model based on the perspectives of the users. Unlike previous studies that use either one of the theories, the integration of the two theories provides a new perspective of understanding the trust factors that influence the use of e-government. This study adopted a survey method, in which questionnaires were analyzed from 631 respondents derived from a stratified random sampling method. Four main hypotheses have been tested and CB-SEM and PLS-SEM have been used for testing and validating the measurement and structure of the EGOV-TRUST model. The study found that there has been a positive relationship between the individual, technological, organizational, environmental dimensions of trust and these factors have positive effects on the use of e-government. It can be concluded that the EGOV-TRUST model has the potential to enhance the usage of e-government among its users. This research contributes to the knowledge of adopting e-government, focusing on deconstructing the element of trust that enhances the usage of e-government. The model can be used as guidelines for governments, especially developing countries for enhancing the usage of e-government among users.